Scale development to asses causal atribution in political participation - Patricia M. Sorribas; Silvina Alejandra Brussino (Revista de Psicología, 2019)
In this paper we develop tools that assess the attributional processes associated with political participation. First, we performed an exploratory study using semi-structured interviews with people with different levels of political engagement. An analysis of the content of the interviews supplied the material which expert judges evaluated in order to identify various attributional statements (A.S.). Second, an instrumental study was implemented, gathering data by a survey (N = 200). A.S. thus obtained were analyzed in order to detect its factorial structure and determine its internal consistency. The developed scales showed a two-factor structure corresponding with the internality-externality dimension and the reliability was acceptable, being more reliable the one which evaluates the attributions relative to the behavior of others.